Perspectives on Poverty in Europe - Stephen P. Jenkins (Institute of Labor Economics (IZA), 2018)
I address four topics: how our capacities to monitor poverty in Europe have improved substantially over recent decades; how progress on EU poverty reduction has been disappointing and why this has been; conceptual and measurement issues; and the future direction of EU-level anti-poverty actions. I follow in the footsteps of a giant – my perspectives are essentially elaborations of points made by Tony Atkinson.
Keywords: C81; D31; I32; 330; poverty; material deprivation; Europe; EU-SILC